Antiplatelet Drugs in the Secondary Prevention of Stroke. Issue 1 (1st February 2002) - Sudlow, Cathie; Hankey, Graeme
Abstract : INTRODUCTION Stroke is a major cause of death and disability in developing and developed countries (Murray & Lopez 1996). Incidence rises steeply with age so that about three quarters of incident strokes occur in people over 65 years of age. In community-based studies among whites, around 80% of strokes are ischaemic, while 15% are due to primary intracerebral haemorrhage, and 5% to subarachnoid haemorrhage (Fig. 1). The proportion of haemorrhagic strokes in the mainly non-white populations of Asia and Africa may be somewhat higher, but ischaemic stroke is still the dominant problem (Sudlow & Warlow 1997). The management of patients with acute ischaemic stroke aims to restore tissue perfusion, minimize cytotoxic brain damage and cerebral oedema, prevent complications of stroke, and prevent a recurrent stroke or other serious vascular event. About 10% of patients with a first-ever acute ischaemic stroke die within 30 days of onset. Most of these early